2020
DOI: 10.3389/fmicb.2020.568457
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Xylooligosaccharide, Xylan, and Whole Wheat Bran on the Human Gut Bacteria

Abstract: Wheat bran is a cereal rich in dietary fibers that have high levels of ferulic acid, which has prebiotic effects on the intestinal microbiota and the host. Herein we explored the effect of xylooligosaccharide, xylan, and whole wheat bran on the human gut bacteria and screened for potential ferulic acid esterase genes. Using in vitro fermentation, we analyzed the air pressure, pH-value, and short-chain fatty acid levels. We also performed 16S rRNA gene and metagenomic sequencing. A Venn diagram analysis reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Bacteroides are major primary degraders of oligo- and polysaccharides with a close relationship with XOS, containing the most expanded glycolytic gene repertoires that target xylan degradation 49 . In fact, different in vitro tests have demonstrated that XOS stimulates Bacteroides growth in the microbial ecosystem 16 , 50 . The abundance of Lachnospiraceae in mice fed a high-fat diet was increased by XOS, increasing the formation of butyric acid in the cecum 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteroides are major primary degraders of oligo- and polysaccharides with a close relationship with XOS, containing the most expanded glycolytic gene repertoires that target xylan degradation 49 . In fact, different in vitro tests have demonstrated that XOS stimulates Bacteroides growth in the microbial ecosystem 16 , 50 . The abundance of Lachnospiraceae in mice fed a high-fat diet was increased by XOS, increasing the formation of butyric acid in the cecum 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Among dietary fiber compounds, xylo-oligosaccharides (XOS) are oligomers composed of 2–6 xylose units linked through β-(1 → 4)-linkages 15 . Their selective fermentation has been shown to induce changes in both composition and activity of the gastrointestinal microbiota, stimulating the growth of butyrate-producing bacteria 16 , 17 . Butyrate has been associated with benefits in intestinal health, such as the modulation of the mucosal inflammatory response and barrier function 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, seven potential FAE genes were identified from in vitro fermentation of human fecal slurry using metagenomic sequencing ( Chen et al, 2020 ) in which one FAE from Alistipes shahii ( As FAE) was characterized ( Wei et al, 2021 ). Here, a novel FAE from Dorea formicigenerans ( Df FAE) of Firmicutes was bacterially expressed and purified to assess its enzymatical properties.…”
Section: Introductionmentioning
confidence: 99%
“…12 Several other reports further proved the existence of FAEs in human intestines. 13,14 In our previous study, an upregulation of seven FAE genes was observed during the in vitro fermentation of fecal slurry using cereal-rich wheat bran, suggesting that FAEs from the intestinal flora play an important role in releasing free FA in foodstuff. 14 In 2004, for the first time, Wang et al isolated, purified, and characterized an FAE from the gut bacterium Lactobacillus acidophilus exhibiting maximum activity at 37 °C and pH 5.6.…”
Section: ■ Introductionmentioning
confidence: 99%
“…13,14 In our previous study, an upregulation of seven FAE genes was observed during the in vitro fermentation of fecal slurry using cereal-rich wheat bran, suggesting that FAEs from the intestinal flora play an important role in releasing free FA in foodstuff. 14 In 2004, for the first time, Wang et al isolated, purified, and characterized an FAE from the gut bacterium Lactobacillus acidophilus exhibiting maximum activity at 37 °C and pH 5.6. 15 Different FAEs from the intestinal flora exhibited distinct activities.…”
Section: ■ Introductionmentioning
confidence: 99%